Modulation of Immune Response in Edible Fish against Aeromonas hydrophila - R Muthu; Rajan MK; S Rajeshwari (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2018)
The present study was to obtain a basic knowledge of the hematology of Catla catla Post challenged with Aeromonas hydrophila. Fish were fed diets representing different supplementation levels of Aegle marmelos fruit extract. The various concentration of fruit extract were 10mg, 20mg and 30mg per 100g for each diet of fi sh. Supplementation of experimental feed after seven days collected from serum in treated fi sh to haematological parameters and biochemical parameters were analysed between control and experiment. The results of challenge test suggest that the fi shes fed with 30mg Aegle marmelos diet had better immunostimulatory activity compared to the control group. Thus, our fi nding confi rms our concentration that Aegle marmelos is a growth promoter and immunostimulant.